2021
DOI: 10.1093/ehjcvp/pvab068
|View full text |Cite
|
Sign up to set email alerts
|

Guided and unguided de-escalation from potent P2Y12 inhibitors among patients with acute coronary syndrome: a meta-analysis

Abstract: Aim Optimal dual antiplatelet therapy (DAPT) in patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) intends to balance ischemic and bleeding risks. Various DAPT de-escalation strategies, defined as switching from a full-dose potent to a reduced dose or less potent P2Y12 inhibitor, have been evaluated in several ACS-PCI trials. We aimed to compare DAPT de-escalation to standard DAPT with full dose potent P2Y12 inhibitors in ACS patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…40 That study was significantly limited because it incompletely differentiated the 2 distinct de-escalation strategies with different timing of de-escalation by meta-regression analyses, and it did not thoroughly assess the critical question of whether the unguided de-escalation strategy is similarly effective and safe compared with the guided selection strategy. 40 Despite the limitation, the study concluded both the guided and unguided de-escalation strategies are safer than DAPT with potent P2Y 12 inhibitors. In contrast, our study performed indirect comparisons through network meta-analysis of the unguided de-escalation strategy and the guided selection strategy.…”
Section: Discussionmentioning
confidence: 99%
“…40 That study was significantly limited because it incompletely differentiated the 2 distinct de-escalation strategies with different timing of de-escalation by meta-regression analyses, and it did not thoroughly assess the critical question of whether the unguided de-escalation strategy is similarly effective and safe compared with the guided selection strategy. 40 Despite the limitation, the study concluded both the guided and unguided de-escalation strategies are safer than DAPT with potent P2Y 12 inhibitors. In contrast, our study performed indirect comparisons through network meta-analysis of the unguided de-escalation strategy and the guided selection strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Although in theory the first alternative is more effective, a recent meta-analysis has suggested that both may be effective. 27 Despite the existence of studies specifically addressing this therapeutic alternative, it still does not have clear support for routine use, as the results of these clinical trials were not able to change clinical practice. 26 For example, the latest American guideline on myocardial revascularization does not include this alternative in the list of possibilities that may be considered to prevent bleeding complications, i.e., it is an alternative without a clearly defined role.…”
Section: De-escalationmentioning
confidence: 99%
“…A recent meta-analysis (5 randomized clinical trials [RCTs], n=10,779) showed that DAPT de-escalation (when: from in-hospital to 1 month post-PCI) vs. standard DAPT with full-dose potent P2Y 12 inhibitor was associated with a significant reduction in Bleeding Academic Research Consortium (BARC) ≥type 2 bleeding (hazard ratio [HR], 0.57; 95% confidence interval [CI], 0.42–0.78) as well as major adverse cardiac events, represented by the composite of CV mortality, myocardial infarction (MI), stent thrombosis, and stroke (HR, 0.77; 95% CI, 0.62–0.96) in ACS patients who underwent PCI. 3) Although the consistency was noted across various de-escalation strategies, it cannot guarantee that this strategy can be applied globally because of its limited power and sample size. 3) …”
mentioning
confidence: 99%
“… 3) Although the consistency was noted across various de-escalation strategies, it cannot guarantee that this strategy can be applied globally because of its limited power and sample size. 3) …”
mentioning
confidence: 99%
See 1 more Smart Citation